The Effect of Reading Aloud on Students’ Reading Comprehension at GKPS 13 Sibarou Junior High School - Erika Sianturi; Rachel Silalahi; Jerico Damanik; Herman Herman; Bernieke Anggita Ristia Damanik; Yanti Kristina Sinaga; Wan Anayati; Rahmawati Rahmawati (Jurnal Pengabdian Nusantara, 2026)
This research investigates how effective the Problem Based Learning (PBL) method is at improving students’ understanding of reading through narrative texts in SMP GKPS 13 Sibarou. The study was motivated by the finding that numerous eighth-grade students struggled with grasping text organization and main concepts in their reading materials. To tackle this challenge, the teacher adopted PBL techniques by offering students real-world problems related to narrative text analysis, which they addressed collectively through reading aloud, discussions, and presentations. The research included 14 students who were paired up, and it utilized worksheets, observation forms, reading comprehension assessments, and documentation as tools. Activities were crafted to encourage students to recognize the organization of narrative texts, apply past tense verbs, and derive meaning through guided inquiry. The reading aloud method aided learners in enhancing their pronunciation, fluency, and understanding of the texts. The findings indicated a significant improvement in students' narrative text comprehension, along with heightened confidence, involvement, and critical thinking skills. The incorporation of PBL encouraged teamwork and a more profound engagement with the content. This method is advantageous for English educators looking to develop meaningful, student-focused learning experiences.